Two men with mules walking the Bonanza Trail through Lousetown, near Dawson, Yukon Territory. - Curtis, Asahel, 1874-1941 (1899)
Klondike Gold Rush. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number